2018
DOI: 10.1007/s00493-016-3594-4
|View full text |Cite
|
Sign up to set email alerts
|

On the Number of Bases of Almost All Matroids

Abstract: For a matroid M of rank r on n elements, let b(M ) denote the fraction of bases of M among the subsets of the ground set with cardinality r. We show thatfor asymptotically almost all matroids M on n elements. We derive that asymptotically almost all matroids on n elements (1) have a U k,2k -minor, whenever k ≤ O(log(n)), (2) have girth ≥ Ω(log(n)), (3) have Tutte connectivity ≥ Ω( log(n)), and (4) do not arise as the truncation of another matroid.Our argument is based on a refined method for writing compressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…We finish our paper by showing that asymptotically almost all matroids have a constant-competitive matroid secretary algorithm. We require two recent results of Pendavingh and van der Pol [20,21].…”
Section: Asymptotic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We finish our paper by showing that asymptotically almost all matroids have a constant-competitive matroid secretary algorithm. We require two recent results of Pendavingh and van der Pol [20,21].…”
Section: Asymptotic Resultsmentioning
confidence: 99%
“…The veracity of Theorem 3 is not terribly surprising, although given the limited tools in asymptotic matroid theory, it is a bit surprising that we can prove it. Indeed, the proof of Theorem 3 relies on recent breakthrough results of Pendavingh and van der Pol [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…And Nelson [19] showed that almost all matroids are nonrepresentable. Pendavingh and van der Pol [20] considered random matroids of rank r and showed that almost all r-sets will be bases in this model.…”
Section: Introductionmentioning
confidence: 99%
“…These are shown in Figure 2.2. Later work by the same authors [23] proved that the same result holds for all uniform matroids.…”
Section: Counting Matroids In Minor-closed Classes (Pendavingh and Van Der Pol's Work)mentioning
confidence: 72%
“…Some progress on asymptotic questions has been made recently, especially by Pendavingh and van der Pol who showed (amongst other things) that asymptotically almost all matroids are k-connected [23], are not a truncation [23], contain a large uniform minor [23], and contain minors isomorphic to each of a small collection of matroids [24].…”
Section: Chapter 1 Introductionmentioning
confidence: 99%